Financial Management in Non-Formal Education: A Narrative Literature Review of Practices and Challenges - Desmawati Desmawati; Tarekah Hasanah; Undang Rosyidin (Indonesian Journal of Education and Youth Development, 2026)
This narrative literature review examines the practices, challenges, and strategies of financial management within non-formal education (NFE) institutions, such as Community Learning Centers (PKBM) and Course and Training Institutions (LKP). Through a systematic search of Google Scholar (2015–2025), the review synthesizes peer-reviewed studies to highlight how financial governance directly impacts institutional sustainability. Key findings reveal a structural gap between operational needs and volatile funding sources, compounded by a widespread lack of accounting competence among NFE administrators. Despite these challenges, emerging best practices demonstrate that institutional resilience can be achieved through funding diversification, particularly via self-sustaining business units and private sector partnerships, and the adoption of digital financial management tools. The study concludes that transitioning from traditional to accountable, technology-assisted financial systems is an urgent imperative for NFE quality reform.